2000
DOI: 10.1128/iai.68.4.2215-2223.2000
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Efficacy inAotusMonkeys of Four RecombinantPlasmodium falciparumVaccines in Multiple Adjuvant Formulations Based on the 19-Kilodalton C Terminus of Merozoite Surface Protein 1

Abstract: The immunogenicity and protective efficacy of four versions of recombinant C-terminal 19-kDa epidermal growth factor-like region of the major surface protein 1 (rMSP119) of Plasmodium falciparum was studied in Aotus monkeys. Vaccination with each of the four rMSP119 constructs elicited high levels of antibodies to MSP119 but only one construct, the 19-kDa fragment expressed as a secreted fusion protein fromSaccharomyces cerevisiae (yP30P2MSP119), induced a high degree of protective immunity in Aotus nancymai a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 26 publications
2
73
0
1
Order By: Relevance
“…Two of these adjuvants, alum and Montanide ISA720, were used previously in malaria vaccine trials for monkeys as well as humans (11,14,21,37). We found that immunization with MSP-Fu 24 induced a significant antibody response with all three adjuvant formulations.…”
Section: Discussionmentioning
confidence: 71%
“…Two of these adjuvants, alum and Montanide ISA720, were used previously in malaria vaccine trials for monkeys as well as humans (11,14,21,37). We found that immunization with MSP-Fu 24 induced a significant antibody response with all three adjuvant formulations.…”
Section: Discussionmentioning
confidence: 71%
“…P. falciparum MSP1 19 -specific invasion inhibitory activity has been shown to be associated with resistance to reinfection in Kenyans (6). Antibody-mediated protection against parasite infection challenge was produced in animal models immunized with either 42-kDa MSP-1 or MSP-1 19 (7)(8)(9)(10)(11). Several studies have shown that MSP-1, especially MSP-1 19 , is a target of protective antibodies against the blood-stage infection (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…This region is the target of some mAbs that have the ability to inhibit the growth of the parasite in vitro (9). In the Aotus monkey challenge model of P. falciparum, MSP1-19 has also proven to protect the animals from infection (10).…”
mentioning
confidence: 99%